2018
DOI: 10.1371/journal.pone.0192130
|View full text |Cite
|
Sign up to set email alerts
|

Differing HIV vulnerability among female sex workers in a high HIV burden Indian state

Abstract: IntroductionThe HIV sentinel surveillance [HSS] conducted in 2010–11 among female sex workers [FSW] in the state of Maharashtra, India provided an opportunity to assess characteristics of different types of FSWs and their HIV risk. It is important for India’s National AIDS Control Program, to understand the differences in vulnerability among these FSW, in order to define more specific and effective risk reduction intervention strategies. Therefore, we analyzed data from HSS with the objective of understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…Another group is indoor-based sex workers who are employed to work in brothels, hotels, massage parlors, saunas, and lodges. In some cases, they might solicit clients independently based on both on-street and off-street, by online advertising in newspapers or by phone or text, or might work for a pimp or manager [ 15 17 ]. FSWs are at greatly elevated risk of acquiring sexually transmitted infections (STIs), including HPV, and their clients can act as a bridging population toward the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Another group is indoor-based sex workers who are employed to work in brothels, hotels, massage parlors, saunas, and lodges. In some cases, they might solicit clients independently based on both on-street and off-street, by online advertising in newspapers or by phone or text, or might work for a pimp or manager [ 15 17 ]. FSWs are at greatly elevated risk of acquiring sexually transmitted infections (STIs), including HPV, and their clients can act as a bridging population toward the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Information about a number of brothels and FSWs was not available, which challenged the calculation of sample size. 12 To resolve it, an approach specifically designed for such population was applied 6 the red light area was mapped for a number of brothels and FSWs. It was found that the area has 2000 FSWs in 330 brothels.…”
Section: Methodsmentioning
confidence: 99%
“…9,17,18 In India, the National AIDS Control Organization (NACO) report documents risk perception in the range of 4%-77% in India and 27%-47% in the study area, higher than the present study's finding. 6 Similarly, a survey in four states of southern India found that 40% FSWs perceived to be at high risk; more so in the state of Andhra Pradesh (56%) and less in Maharashtra (18%). 1 With the implementation of the HIV prevention interventions in the study area for more than two decades, this finding is significant.…”
Section: Non-risk Perceptionmentioning
confidence: 98%
See 1 more Smart Citation
“…8 FSWs also have the lowest levels of adherence to ART. 9,10 Other factors that may complicate the lives of FSWs include poverty, 11 illiteracy, 12 human trafficking, 13 violence, 14 arrest, 15 food insecurity, [16][17][18] stigma 19,20 and mental health struggles such as depression, 21,22 alcohol 23,24 and/or substance abuse. [25][26][27] Several of these factors, including food insecurity and depression, have been shown in some studies to be associated with ART adherence.…”
Section: Introductionmentioning
confidence: 99%